Natural Compounds as Antimicrobial Agents, 2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
After a succesful first volumne of the Special Issue titled "Natural compounds as Antimicrobial Agents", we are pleased to publish a second edition, which focuses on specific aspects of this research area, such as the fight against nontuberculous mycobacteria; antimicrobials from toads; apitoxins as antimicrobials; the fight against parasites such as Trypanosma cruzi or Schistosoma mansoni; the fight against fungi; the use of coral-origin bacteria with antimicrobial volatile compounds; the fight against Clostridium perfringens; the productive effect of L carnitine, which has antimicrobial properties; and the effect of fennel waste extracts against bacteria such as Salmonella, E. coli, or S.aureus in beef burgers.